Chemical Reactions of Cationic Metallofullerenes: An Alternative Route for Exohedral Functionalization. Issue 8 (24th January 2020) - Hu, Yajing; Solé‐Daura, Albert; Yao, Yang‐Rong; Liu, Xuechen; Liu, Sijie; Yu, Ao; Peng, Ping; Poblet, Josep M.; Rodríguez‐Fortea, Antonio; Echegoyen, Luis; Li, Fang‐Fang
Abstract: The chemistry of cationic forms of clusterfullerenes remain less explored than that of the corresponding neutral or anionic species. In the present work, M3 N@ Ih ‐C80 (M=Sc or Lu) cations were generated by both electrochemical and chemical oxidation methods. The as‐obtained cations successfully underwent the typical Bingel–Hirsch reaction that fails with neutral Sc3 N@ Ih ‐C80 . Two isomeric Sc3 N@ Ih ‐C80 cation derivatives, [5, 6]‐open and [6, 6]‐open adducts, were synthesized, and the former has never been prepared by means of a Bingel–Hirsch reaction with neutral clusterfullerenes. In the case of the Lu3 N@ Ih ‐C80 cation, however, only a [6, 6]‐open adduct was obtained. Density functional theory (DFT) calculations indicated that the oxidized M3 N@ Ih ‐C80 was much more reactive than the neutral compound upon addition of the diethyl bromomalonate anion. The Bingel–Hirsch reaction of M3 N@ Ih ‐C80 cations occurred by means of an unusual outer‐sphere single‐electron transfer (SET) process from the diethyl bromomalonate anion to the stable intermediate [M3 N@C80 (C2 H5 COO)2 CBr] . . Remarkably, the diethyl bromomalonate anion was found to act as both a nucleophile and an electron donor. Abstract : The chemistry of cationic forms of clusterfullerenes is explored in terms of formation, reactivity and regioselectivity. M3 N@ Ih ‐C80 (M=Sc or Lu) cations were generated by both electrochemical and chemical oxidation. The as‐obtained cations successfully undergo the typical Bingel–Hirsch reaction that fails with neutral Sc3 N@ Ih ‐C80 . The reaction of the cations occurs by means of an unusual outer‐sphere single‐electron transfer process.